Investigating Strategies Used by Libyan EFL Teachers in Teaching Reading Comprehension at Sirte Basic Education Schools - Mariam Akilah Omar (Abhat Journal, 2018)
This study aims at finding out the strategies used by English language teachers in teaching reading comprehension to basic education pupils in Sirte, Libya. Towards this purpose two research designs have been used: qualitative and quantitative by using two data collection methods: a teachers' questionnaire and a classroom observation. In this study 26 English language teachers from Sirte Basic education schools participated in the study to answer the questionnaire moreover, three sets of Class Nine students in three schools - randomly chosen among the basic education schools in Sirte - were observed for at least five times.. The results of the data collected show that teachers use different teaching strategies in teaching reading comprehension. These strategies comprise of the teaching of new vocabulary, reading aloud and answering the comprehension questions.